Self on audio : the collected audio design articles of Douglas Self - Self, Douglas (Focal Press, 2016)
Self on Audio: The collected audio design articles of Douglas Self , Third Edition is the most comprehensive collection of significant articles in the technical audio press. This third edition features 45 articles that first appeared in Elektor , Linear Audio , and Electronics World . Including expanded prefaces for each article, the author provides background information and circuit commentary. The articles cover both discrete and opamp preamplifier design, mixing console design, and power amplifier design. The preamplifier designs are illuminated by the very latest research on low noise and RIAA equalization. The famous series of 1993 articles on power amplifier distortion is included, with an extensive commentary reflecting the latest research on compensation and ultra-low distortion techniques. This book addresses the widened scope of technology that has become available to the audio designer over the last 35 years. New materials include: Prefaces that explain the historical background of the articles, why they were written, and the best use of the technology of the day Extensive details, including schematics, of designs that preceded or followed the design in each article, giving an enormous amount of extra information and a comprehensive overview of how author's design approaches have evolved New directions for the technology, describing new lines of thought such as curvilinear Class-A.